Electrification in Rural Areas Using Realistic Equipments - Singh, Jay; Chatterjee, Kalyan; Singh, Ramveer (International Journal of Engineering and Technology, 2018)
This paper presents a method of low cost setup for the generation of the electricity via Biogas in rural areas. The proposed setup requires easily available items in the villages. In this paper, authors have suggested a technique to minimize the running cost of the electricity generation system. The superiority of the proposed method is to reduce diesel quantity as much as possible, which may further reduce the capital cost and also making pollution free environment.Â